Letters of Blood and Other Works in English - Svensson, Lars-Håkan (Open Book Publishers, 2011)
This collection brings together for the first time select works in English by the major Swedish modernist poet and critic Göran Printz-Påhlson. It was Printz-Påhlson who introduced poetic modernism to Scandinavia, and his essays and poems delve deeply into English, American, and continental modernist traditions. As well as Letters of Blood, the collection includes the full text of "The Words of the Tribe", a major statement on modern poetics, in which Printz-Påhlson explores the significance of primitivism in Romanticism and Modernism, and the nature of metaphor and literary materialism. The collection also includes essays on style, irony, realism, and the relationship between historical drama and historical fiction, as well as studies of American poetry. Printz-Påhlson's poetry in English continues to explore these themes by different, often surprisingly innovative, means.